Clothing - Saracino, Michele, 1971- (Book collections on Project MUSE., 2012)
Reinhold Niebuhr argued that one of the fundamental challenges to human existence is the anxiety caused by our desire to be perfect and godlike while knowing we are limited and mortal. This book explores how human adornment practices negotiate anxieties about our finitude. Through our clothing, we often shield ourselves from feeling our human frailty and from having others detect our emotional, physical, and spiritual vulnerabilities. Looking at the incarnation as a form of "dress," Saracino claims that getting naked with Jesus or embracing our vulnerability is our only hope at creating life-g